Proposal for the creation of a (CSIRT) for the government sector (Nexo Revista Científica, 2023)
The present investigation proposes the creation of a cyber incident response center (CSIRT), in the government sector, given the vulnerabilities and economic losses suffered by governments, due to the threats of Hacking in cyberspaces, in clear violation of the sovereignty of the systems and the data of the state government, therefore this investigation, we will direct it through a case study, in which we will determine the foundations and the feasibility of implementing the CSIRT project in the country of Nicaragua, to achieve our objective we will deploy a survey of officials of the ICT department, of government entities, to collect detailed information, regarding the preparation of cybersecurity, administrative procedures or guidelines, aligned to a disaster recovery plan, in prevention and action responses to cyber-attacks, classifying the levels of affectation, in hindering the continuity process continuity of the business, in this case the basic traditional and online government services.